Making Money Through Write Books With AI - zakee putri (Journal of Artificial Intelligence and Development, 2023)
In the realm of literary innovation, harnessing the power of Artificial Intelligence (AI) to create and monetize written content is a burgeoning frontier. The process involves leveraging advanced algorithms and natural language processing capabilities to generate engaging and coherent narratives. By tapping into the realm of AI-generated literature, authors and content creators can not only streamline the writing process but also explore new dimensions of creativity. This paradigm shift in the traditional authorship landscape opens up opportunities for individuals to make money by embracing the synergy between human ingenuity and AI capabilities. As the literary world continues to evolve, the prospect of financial success through the collaborative efforts of authors and AI heralds a dynamic era where technology and creativity intersect, paving the way for a novel approach to writing books and redefining the economic landscape of the publishing industry.